Los proyectos para el embellecimiento arquitectónico de la Ciudad de México, 1877-1911: la construcción de la "Porfiriopolis" - Rivera Valencia, Eynar (Universidad Autónoma Metropolitana, 2006)
During the last third of the XIX century, Mexico City underwent one of the most significant changes of its history, both regarding the architectural and urban aspects of its structure. This change was due to the fact that the leading Mexican elite had witnessed the economic, industrial, artistic and cultural developments reached in countries such as France, Great Britain, the United States, etc, then, attempting to enter into this glamorous world and inspired by Positivism, they set out to transform the capital of the Republic as far as its structure and physical appearance were concerned. In other words, they embellished it. Based on the completion of ambitious urban and architectonic projects they were building what became known as the “Porfiriopolis”. The “Porfiriopolis” was that city that intended to be the tangible result of the progress achieved by the present political regime headed by General Porfirio Díaz, because, on the one hand, with the encouragement of this type of constructions, the high cultural level of the Nation would be manifest, and on the other, Mexico would give the image of a highly civilized country. In order to achieve all this, they tried to improve the public tax gathering system because due to its healthy state it would be possible for the local and federal governments to embark in the construction of monumental public buildings and city ornaments. In this manner there appeared new urban spaces inspired in similar spaces planned for cities such as Paris and Chicago. These projects were designed by private enterprises and were regulated by the Mexico City government. Constructions such as gardens and park, and ample and well delineated avenues were contemplated. The planning of these spaces proved to be a very profitable business for those promoting new living enclosures, due to the fact that they not only projected these spaces but also planned and projected the constructions which will be placed within them, and they as well, financed the purchase of the land required for these constructions. All these buildings improved immensely the appearance of the entire metropolis. The government of the Republic also built a whole set of buildings that satisfied the administrative, supply, security, education and public welfare needs of the population. Because these aspects had already been contemplated in every first rate urban centre in the world and the ever growing population of the city also demanded their existence. Based on this type of architectural developments in the metropolis, the entire economic and cultural development of the country was projected, therefore these constructions were of sufficiently large dimensions, excellent design and good taste, in such a way that these characteristics were outstanding in those monumental constructions destined for the public welfare, health and public administration, because greater care was taken in regards to their ornamentation and dimensions.; En el último tercio del siglo XIX, la ciudad de México sufrió uno de los cambios más significativos de su historia, tanto en materia urbana como arquitectónica; debido a que las clases dirigentes mexicanas, vislumbraron los alcances obtenidos en cuanto a desarrollo económico, industrial, artístico y cultural alcanzado por países como Francia, Gran Bretaña, Estados Unidos, etc., en su intento por incursionar a este fastuoso mundo e inspirados por la doctrina del positivismo, se dieron a la tarea de transformar a la capital de la Republica tanto en su estructura como en su apariencia en otras palabras la embellecieron. A partir de la realización de ambiciosos proyectos urbanos y arquitectónicos se fue construyendo lo que se denomino como “Porfiriopolis”, esa ciudad que pretendió ser el vivo reflejo del progreso logrado por el régimen y cuya cabeza política era Porfirio Díaz; puesto que con el fomento de este tipo de obras se proyectaría por una parte el alto grado de cultura de la nación y por la otra, cuan civilizado se encontraba el país; razón por la cual, se procuró en primera instancia mejorar la hacienda pública porque a partir de su buen estado seria posible hacer que todas aquellas obras publicas emprendidas por el gobierno local y federal, fueran de gran monumentalidad. De esta forma, surgieron nuevos espacios urbanos inspirados en las planeaciones realizadas en ciudades como Paris y Chicago, proyectados por particulares y regulados por el gobierno de la ciudad de México, en donde se contemplaron jardines, calles amplias y bien trazadas, siendo un negocio muy rentable para los promotores de estos nuevos espacios habitacionales, debido a que no sólo se dieron a la tarea de proyectar dichos espacios urbanos, sino que planearon las construcciones que se alojarían dentro de ellos y financiaron la compra de estas propiedades, con lo que se contribuyó de manera significativa a mejorar la apariencia de la metrópoli. Asimismo, el Gobierno de la Republica edificó en la urbe todo un conjunto de establecimientos que satisficieran las necesidades administrativas, de abasto, seguridad, salud, la instrucción y la beneficencia pública; puesto que fueron aspectos que en toda urbe de primer nivel habían sido contemplados y que la creciente población de la ciudad demandaba. A partir de este tipo de obras arquitectónicas en la metrópoli, se pretendió proyectar todo el desarrollo económico y cultural del país, razón por la cual, se procuró que todas ellas fueran de buenas proporciones, excelente diseño y buen gusto; de tal manera que dichas cualidades sobresalieron en aquellas obras monumentales como los destinados a la beneficencia, la salud y la administración pública, puesto que se prestó mayor atención y cuidado en lo que respecta a su ornamentación y dimensiones.